POLYMERS IN DENTISTRY: CHARACTERISTICS, CLASSIFICATION, AND CLINICAL SIGNIFICANCE - Chakkanov Fakhritdin Khusanovich; Makhmudov Bekzod (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Polymers (from poly... + Greek meros — fraction, part) — substances, the molecules (macromolecules) of which consist of a large number of repeating units. Polymers are the basis of plastics, chemical fibers, rubber, paint and varnish materials, adhesives. At the same time, there are 2 main mechanisms for obtaining polymers: through polyaddition and polycondensation. The creation of polymers for dentistry often leads to the development of materials that have found application in other fields of medicine and technology. Such an example is the development of epoxy resins, as well as fast-curing compositions of an amine peroxide system, which are now widely used in engineering and medicine. The main starting compounds for the production of polymeric dental materials are monomers and oligomers [mono-, di-, tri- and tetra(met)acrylates]. Monoacrylates are volatile, so they are used in combination with high molecular weight esters, which reduces polymer shrinkage. Di-[tri-, tetra-](met) acrylates are found in most composite restoration materials, as well as in basic plastics as crosslinking agents.